Aprovechamiento de vertebrados terrestres por las poblaciones humanas que habitaron la costa del Golfo San Matías (Río Negro, Argentina) durante el Holoceno tardío - Marani, Hernán A., (South American archaeology series ;, 2018)
This text presents the results and discussion of archaeofaunal studies which took place in the northern San Matías Gulf (Río Negro Province) during the last six years, focusing on terrestrial mammals and birds.